BARRIERS IN MUTUAL TRADE IN ELECTRIC ENERGY IN THE FRAMEWORK OF THE COMMON ELECTRIC POWER MARKET OF THE EURASIAN ECONOMIC UNION - D. Arifulova; A. Storozhenko (Вестник университета)
The mutual trade in electricity between the Russian Federation and other members of the Eurasian Economic Union is considered. The existing barriers to the formation of the common electric power market of the Eurasian Economic Union have analysed. The possible variants of centralized electricity trading under fixedterm contracts and day ahead market have considered. Both positive and negative effects for the domestic electricity market have identified as the result of the formation of the common electric power market of the Eurasian Economic Union.